Glycyrrhizic acid alleviates bleomycin-induced pulmonary fibrosis in rats - Gao, Lili; Tang, Haiying; He, Huanyu; Liu, Jia; Mao, Jingwei; Ji, Hong; Lin, Hongli; Wu, Taihua (Frontiers in Pharmacology, 2015)
Idiopathic pulmonary fibrosis is a progressive and lethal form of interstitial lung disease that lacks effective therapies at present. Glycyrrhizic acid (GA), a natural compound extracted from a traditional Chinese herbal medicine Glycyrrhiza glabra, was recently reported to benefit lung injury and liver fibrosis in animal models, yet whether GA has a therapeutic effect on pulmonary fibrosis is unknown. In this study, we investigated the potential therapeutic effect of GA on pulmonary fibrosis in a rat model with bleomycin (BLM)-induced pulmonary fibrosis. The results indicated that GA treatment remarkably ameliorated BLM-induced pulmonary fibrosis and attenuated BLM-induced inflammation, oxidative stress, epithelial-mesenchymal transition and activation of tansforming growth factor-beta signaling pathway in the lungs. Further, we demonstrated that GA treatment inhibited proliferation of 3T6 fibroblast cells, induced cell cycle arrest and promoted apoptosis in vitro, implying that GA-mediated suppression of fibroproliferation may contribute to the anti-fibrotic effect against BLM-induced pulmonary fibrosis. In summary, our study suggests a therapeutic potential of GA in the treatment of pulmonary fibrosis.